2020
DOI: 10.48022/mbl.2003.03010
|View full text |Cite
|
Sign up to set email alerts
|

Purification, Characterization and Immobilization of Lipase from Proteus vulgaris OR34 for Synthesis of Methyl Oleate

Abstract: A newly isolated strain, Proteus vulgaris OR34, from olive mill waste was found to secrete an alkaline extracellular lipase at 11 U• ml -1 when cultivated on an optimized liquid medium. This lipase was purified 94.64fold with a total yield of 9.11% and its maximal specific activity was shown to be 3232.58 and 1777.92 U•mg -1 when evaluated using the pH-stat technique at 55℃ and pH 9 and Tributyrin TC4 or olive oil as the substrate. The molecular mass of the pure OR34 lipase was estimated to be around 31 kDa, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 81 publications
1
1
0
Order By: Relevance
“…However, Novozym 435 exhibited preference for short chain fatty acids and long chain fatty acids, as reported by Wu et al [62]. Duan et al [63], Misbah et al [64] and Rivero-Pino et al [65] found that many lipases had substrate specificity toward triacylglycerols with short or medium carbon chain during the hydrolysis of triacylglycerols. While for the hydrolysis of fatty acid esters, lipases expressed different selectivity.…”
Section: Substrate Specificity Of Lipasesupporting
confidence: 57%
“…However, Novozym 435 exhibited preference for short chain fatty acids and long chain fatty acids, as reported by Wu et al [62]. Duan et al [63], Misbah et al [64] and Rivero-Pino et al [65] found that many lipases had substrate specificity toward triacylglycerols with short or medium carbon chain during the hydrolysis of triacylglycerols. While for the hydrolysis of fatty acid esters, lipases expressed different selectivity.…”
Section: Substrate Specificity Of Lipasesupporting
confidence: 57%
“…Protease enzymes are one of the virulence factors for proteus [9]. One of these types of protein-degrading enzymes is the Metalloprotease enzyme, where this enzyme works to analyze proteins that contain metal ions in their composition, such as Na+, K+, which are essential in pathogenesis [10] Proteus secretes the enzyme lipase [11] [12], which includes lipolytic enzyme (general) Lipases and specialized enzyme phospholipases. Lipase enzymes work to break down the ester bonds that bind fatty acids with glycerol, producing a molecule of glycerol and fatty acids [3].…”
Section: Introductionmentioning
confidence: 99%